(untitled) (Journal of Atomic and Molecular Sciences, 2013)
With the help of cross-Kerr nonlinearities and homodyne measurement, we propose a scheme to generate three-photon GHZ states. Under the same framework, multi-photon GHZ state can be also realized. Compared with the previous ones, our scheme is much more simplified and lower errors. Moreover, only some linear elements and weak cross-Kerr mediums are employed, which make our scheme more feasible in the experiment.